Aaron Rosenberg y Leslie F. Zubieta, eds. 2021. África: nuevos horizontes de la etnografía mexicana. Ciudad de México: El Colegio de México. 197 pp. ISBN 9786075642949 - Reyes Lugardo, Marco Antonio (Estudios de Asia y África, 2022)
Aaron Rosenberg y Leslie F. Zubieta, eds. 2021. África: nuevos horizontes de la etnografía mexicana. Ciudad de México: El Colegio de México. 197 pp. ISBN 9786075642949